Lay readings of the Bible in early modern Europe
1 online resource.
Keywords: "The aim of this collection of essays is to bring together new comparative research studies on the place and role of the Bible in early modern Europe. It focuses on lay readings of the Bible, interrogating established historical, social, and confessional paradigms. It highlights the on-going process of negotiation between the faithful congregation and ecclesiastical institutions, in both Protestant and Catholic countries. It shows how, even in the latter, where biblical translations were eventually forbidden, the laity drew upon the Bible as a source of ethical, cultural, and spiritual inspiration, contributing to the evolution of central aspects of modernity. Interpreting the Bible could indeed be a means of feeding critical perspectives and independent thought and behavior".